Revision of Palaearctic species of the genus Cionus Clairville (Coleoptera: Curculionidae: Cionini) - Košťál, Michael; Caldara, Roberto (Zootaxa, 2019)
Palaearctic species of the genus Cionus Clairville, 1798 are revised and 61 species are recognized as valid. Sixteen species are described as new to science: Cionus armeniacus sp. n., C. boroveci sp. n., C. colonnellii sp. n., C. dodeki sp. n., C. harani sp. n., C. himalayensis sp. n., C. khorasanicus sp. n., C. laibalei sp. n., C. maurus sp. n., C. negevicola sp. n., C. neglectus sp. n., C. osmanlis sp. n., C. rossicus sp. n., C. rufescens sp. n., C. winkelmanni sp. n. and C. yunnanensis sp. n. Cionus auriculus Reitter, 1904 stat. n. is resurrected from the synonymy of C. hortulanus (Geoffroy, 1785), C. atlanticus Peyerimhoff, 1926 stat. prom. is raised to specific rank from C. longicollis atlanticus, C. montanus Wingelmüller, 1914 stat. prom. is raised to specific rank from C. longicollis montanus, C. affinis Brahm, 1790 syn. n. is synonymized with C. scrophulariae (Linnaeus, 1758), C. franzi A. Hoffmann, 1960 syn. n. with C. hortulanus (Geoffroy, 1785), C. inexspectatus Tempère, 1961 syn. n. with C. leonhardi Wingelmüller, 1914, C. pulverosus densenotatus Reitter, 1914 syn. n. with C. pulverosus Guérin-Méneville, 1833, C. schoenherri laportei A. Hoffmann, 1953 syn. n. with C. schoenherri C. N. F. Brisout de Barneville, 1863, C. schultzei nuristanus Voss, 1937 syn. n. with C. dependens Faust, 1886, C. scrophulariae albosuturatus Roubal, 1936 syn. n. with C. scrophulariae (Linnaeus, 1758), C. subsquamosus Reitter, 1914 syn. n. with C. hortulanus (Geoffroy, 1785), C. thapsus semialbellus Reitter, 1904 syn. n. with C. gebleri Gyllenhal, 1838, C. thapsus tissoni Reitter, 1904 syn. n. with C. thapsus (Fabricius, 1792). Neotypes of Cionus griseopubens Wingelmüller, 1914, Cionus ungulatus Germar, 1821, Cionus villae Comolli, 1837, Curculio affinis Brahm, 1790, Curculio alauda Herbst, 1784, Curculio bipustulatus Marsham, 1802 and Curculio tuberculosus Scopoli, 1763 are designated. Curculio thapsus Fabricius, 1792 (currently Cionus) is formally proposed as nom. protectum and Curculio assimilis Harrer, 1784 as nom. oblitum. Redescriptions, comparative morphology, distributions, biological notes and key to all Palaearctic species are given.
Keywords: brouci; Orthoptera; Coleoptera, Curculionidae, Curculioninae, Cionini, Cionus, Palaearctic region; Animals; Weevils; zvířata; nosatcovití; Coleoptera